ATP Alters the Oxylipin Profiles in Astrocytes: Modulation by High Glucose and Metformin - Alexey I. Drozhdev; Vladislav O. Gorbatenko; Sergey V. Goriainov; Dmitry V. Chistyakov; Marina G. Sergeeva (Brain Sciences)
Background: Astrocytes play a key role in the inflammatory process accompanying various neurological diseases. Extracellular ATP accompanies inflammatory processes in the brain, but its effect on lipid mediators (oxylipins) in astrocytes remains elusive. Metformin is a hypoglycemic drug with an anti-inflammatory effect that has been actively investigated in the context of therapy for neuroinflammation, but its mechanisms of action are not fully elucidated. Therefore, we aimed to characterize the effects of ATP on inflammatory markers and oxylipin profiles; determine the dependence of these effects on the adaptation of astrocytes to high glucose levels; and evaluate the possibility of modulating ATP effects using metformin. Methods: We estimated the ATP-mediated response of primary rat astrocytes cultured at normal (NG, 5 mM) and high (HG, 22.5 mM) glucose concentrations for 48 h before stimulation. Cell responses were assessed by monitoring changes in the expression of inflammatory markers (TNFα, IL-6, IL-10, IL-1β, iNOS, and COX-2) and the synthesis of oxylipins (41 compounds), assayed with ultra-high-performance liquid chromatography and tandem mass spectrometry (UPLC-MS/MS). Intracellular pathways were assessed by analyzing the phosphorylation of p38; ERK MAPK; transcription factors STAT3 and NF-κB; and the enzymes mediating oxylipin synthesis, COX-1 and cPLA2. Results: The stimulation of cells with ATP does not affect the expression of pro-inflammatory markers, increases the activities of p38 and ERK MAPKs, and activates oxylipin synthesis, shifting the profiles toward an increase in anti-inflammatory compounds (PGD2, PGA2, 12-HHT, and 18-HEPE). The ATP effects are reduced in HG astrocytes. Metformin potentiated ATP-induced oxylipin synthesis (11-HETE, PGD2, 12-HHT, 15-HETE, 13-HDoHE, and 15-HETrE), which was predominantly evident in NG cells. Conclusions: Our data provide new evidence showing that ATP induces the release of anti-inflammatory oxylipins, and metformin enhances these effects. These results should be considered in the development of anti-inflammatory therapeutic approaches aimed at modulating astrocyte function in various pathologies.